Evaluation of passion fruit jelly stability added from passion fruit and inulina peel flour by physical, physical-chemical and microbiological indicators (Research, Society and Development, 2022)
Among the fruits produced in Brazil, passion fruit can be used to prepare the most diverse products. Jelly, for example, has become an alternative to fruit utilization by providing increased shelf life and adding value to the product through whole fruit or its residues when they have technological value. Passion fruit rind is rich in pectin, fiber and carbohydrates. Inulin is a soluble fiber, commonly extracted from chicory or artichoke, which offers several nutritional and technological benefits. With the growing search for foods with functional properties and the significant amount of residues generated by the industries, the objective was to elaborate a passion fruit jelly added to the flour of its shell and inulin and to evaluate its stability. The physical and physicochemical parameters were titratable acidity, pH, water activity, soluble solids, water content, reducing and non-reducing sugars. of mold and yeast. All formulations were found to comply with the standards established by the legislation for fruit jellies, except for pH, which only formulation F4 was adequate. In conclusion, jelly with 1% of passion fruit rind flour and 4% inulin is the most viable for industrial scale production.